2022
DOI: 10.14426/cristal.v10i1.419
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to research access during COVID-19: Interviewing students with disabilities in South African higher education

Sibonokuhle Ndlovu

Abstract: Carrying out research using face-to-face interviews with students with disabilities has been most difficult in higher education during COVID-19 pandemic. This paper seeks to answer the question: what are the barriers confronted by researchers in conducting interview research with students with disabilities in South African higher education during the COVID-19 pandemic? Data were collected by analysing and synthesising South African and international literature available in Research Gate, ERIC, JSTOR, Sabinet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This means that social, physical, academic and institutional environments are still restricted for some social groups, more particularly the previously disadvantaged, including those with disabilities. Literature has revealed that students with disabilities are confronted by challenges in learning (Mutanga, 2017;Ntombela, 2020;Ndlovu, 2020c), when doing fieldwork , in research engagement (Ndlovu, 2022) and limited by infrastructure (Hall & Belch, 2000;Fitchett, 2015). As already indicated, teaching and learning and research are practices that are a continuum and involve both students and academics.…”
Section: South African Higher Education Context During Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that social, physical, academic and institutional environments are still restricted for some social groups, more particularly the previously disadvantaged, including those with disabilities. Literature has revealed that students with disabilities are confronted by challenges in learning (Mutanga, 2017;Ntombela, 2020;Ndlovu, 2020c), when doing fieldwork , in research engagement (Ndlovu, 2022) and limited by infrastructure (Hall & Belch, 2000;Fitchett, 2015). As already indicated, teaching and learning and research are practices that are a continuum and involve both students and academics.…”
Section: South African Higher Education Context During Transformationmentioning
confidence: 99%
“…For example, academics with totally hearing impairment who use sign language have more challenges than Sibonokuhle Ndlovu those with the same impairment at a mild level who may use oral language, can sign-or lip read. The literature revealed that it is students with total loss of hearing who experience greater communication challenges when conducting research with participants who have a hearing sense (Ndlovu, 2022). In addition, academics with disabilities from disadvantaged backgrounds confront more challenges in doing research or community engagement because of lack of adequate resources.…”
Section: Intersectionality and Challenges For Academics With Disabili...mentioning
confidence: 99%